Resection of a Catecholamine-Elaborating Retroperitoneal Paraganglioma Invading the Inferior Vena Cava - E. M. Mannina; Z. Xiong; R. Self; E. Kandil (Case Reports in Surgery)
Paragangliomas are rare tumors originating outside of the adrenal medulla which can be associated with catecholamine secretion or mass effect, one of which typically leads to their discovery. The differences between these tumors and traditional intra-adrenal pheochromocytomas are a subject of recent investigations. Standard of care therapy is medical management and surgical resection of the tumor. When tumors are biochemically active, medical optimization of the autonomic nervous system is a critical component to a safe, definitive resection. Tumors arising in the retroperitoneum present technical challenges for the surgeon as they are often large and difficult to access, making an oncologic resection much more difficult. Lastly, these tumors are mostly benign and rarely invade adjacent structures—an operative finding not always predicted by preoperative imaging—which, if present, adds significant complexity and risk to the resection. A case illustrating these challenges in the management of a biochemically active retroperitoneal paraganglioma invading the inferior vena cava follows.